The influence of smartphone use on academic performance among Indonesian university students - Morissan (Penerbit Universiti Kebangsaan Malaysia, 2020)
University students use smartphones at every opportunity including in the lecture hall when they’re attending courses. This study hypothesizes that there is a significant influence of smartphone use on academic performance. However, in assessing the influence, several other variables need to be considered such as gender, smoking habits, self-efficacy, academic efficacy, and romantic relationships. The sample of this study was students (N = 582) who were domiciled in Jakarta and surrounding areas (Jabodetabek). All analyses were carried out using SPSS through the following steps. First, the independent sample t-test and ANOVA were performed to examine the academic performance differences on three predictors: (1) sex, (2) smoking habit, and (3) romantic relationship. Second, hierarchical multiple regression was used to answer the research question whether or not there was a significant influence of smartphone use on academic performance by controlling the overall predictor variable? The results show that among smartphone user students, the female group showed better academic performance, as did students without romantic partners, and did not smoke. Calculation with multiple hierarchical regression shows that among all predictors examined, smoking behaviour is the most significant moderator variable in influencing academic performance (β = -0.22, p<0.001), followed by cellphone use (β = 0.14, p<0.001).